Advances in solar pond technology and prospects of efficiency improvement methods - Mbelu, Onyedika V.; Adeyinka, Adekanmi M.; Yahya, Daniel I.; Adediji, Yaqub B.; Njoku, Howard (Renewables : wind, water, and solar, 2024)
The rising global energy demand necessitates innovative solutions for harnessing renewable energy sources. Solar ponds have received attention as they present a viable means to address this challenge by absorbing and storing solar radiation. This article provides a comprehensive review of solar pond technology, including its principles, applications, heat extraction mechanisms, and approaches to optimize performance, with special attention to the salt-gradient solar pond. Additionally, the article identifies challenges that currently hinder the large-scale adoption of solar pond technology and offers recommendations for future research. By providing a detailed analysis of the current trends and future research directions, this paper seeks to contribute to the ongoing efforts to improve these systems, exploring various approaches to increase their efficiency and make them more economical and environmentally sustainable.